ETIKA PENGGUNA DAN STRATEGI MITIGASI VANDALISME DI PERPUSTAKAAN SEKOLAH: STUDI KASUS SMP NEGERI 2 AMPEK ANGKEK - Kristin Natalia Hutahaean; Hensawaty Elviana Br Sihombing; Sherly Fanny Annisa; Mutiara Antika; Syifa Azzahra (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2025)
School libraries play an important role in supporting the learning process and developing students’ literacy. However, unethical user behavior, such as vandalism of library materials, still frequently occurs and can reduce the quality of services and the comfort of other users. This study aims to analyze user ethics and the efforts to prevent and address vandalism at the Library of SMP Negeri 2 Ampek Angkek. The research employed a descriptive qualitative method through interviews with the head librarian as the main source of information regarding user behavior and ethics. The results show that common forms of vandalism include scribbling, tearing, and removing pages from books. The contributing factors include students’ lack of awareness in maintaining collections, the unstable nature of adolescence, and a low sense of responsibility toward library facilities. The library has implemented several preventive measures, including socialization of user ethics, the application of educational sanctions, and increased supervision of collections. It can be concluded that the enforcement of strict regulations and continuous ethical guidance can improve students’ awareness in maintaining collections and reduce acts of vandalism in school libraries.